Using eDNA to find Micrognathozoa - Giribet, Gonzalo; Wangensteen, Owen S.; Garcés-Pastor, Sandra; Møller, Peter Rask; Worsaae, Katrine (Current biology, 2023)
Over the past decades the sampling of environmental DNA (eDNA) — encompassing the DNA of all organisms present in an environmental sample1 — has emerged as a technique for biodiversity monitoring and discovery in a diversity of environments. Avoiding the physical collection and identification of biota, this approach is praised for its independence of taxonomic expertise and has changed the way biologists study biodiversity. However, a common result in eDNA studies is the finding of unexpected taxa which are often removed by conservative bioinformatic filters or disregarded, since the authors are uncertain about the result and rarely have the interest, time, skills, and/or resources to return to the field and confirm with actual specimens2. Here, we report a case in which an eDNA discovery led to the physical localization of a member of the Micrognathozoa (Figure 1B) — a rare group of limnic micrometazoans, and the animal phylum to be discovered last3, which is the sister group to rotifers4,5. To this day, Micrognathozoa still comprises only a single named species from Greenland and a few additional disparate places. Gonzalo Giribet and colleagues report on finding the elusive micrognathozoa based on an eDNA signal in a Pyrenean bog.